Development of separation methods for the chiral resolution of hexahelicenes - Storch, Jan; Kalíková, Květa; Tesařová, Eva; Maier, Vítězslav; Vacek, Jan (Journal of chromatography. A, Including electrophoresis and other separation methods, 2016)
In this short communication we report optimized procedures for the chiral separation of non-charged [6]helicene (1) and cationic derivative 1-butyl-3-(2-methyl[6]helicenyl)-imidazolium bromide (2) using high-performance liquid chromatography (HPLC) and supercritical fluid chromatography (SFC) methods. The possibility of using capillary electrophoresis (CE) was also tested. The satisfactory results were obtained with SFC, where the highly selective resolution of four enantiopure 1 and 2 helicenes was achieved in a single run within 5min. The semi-preparative procedure for the isolation of P and M enantiomers of compound 2, including circular dichroism data, is reported here for the first time. The results could be used in further separations and analytical applications targeting carbohelicenes vs. positively charged helicene derivatives.
Keywords: Chromatography, Supercritical Fluid; elektroforéza kapilární; polycyklické sloučeniny; superkritická fluidní chromatografie; Electrophoresis, Capillary; Stereoisomerism; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; Polycyclic Compounds; stereoizomerie